A retrospective cohort study of bacterial native vertebral osteomyelitis and its management in the UK. (November 2021) - Bousfield, Rachel; Ramsay, Isobel; Warne, Ben; Kotecha, Deevia; Mitchell, Tamara; Sandoe, Jonathan; Moore, Elinor; Nickerson, Emma; Kirby, Andrew; Enoch, David; ,
Highlights: Causative organisms can be elusive, despite blood cultures and biopsy. Those patients with greater comorbidities have higher rates of treatment failure. Over half of patients experienced complications and 6% died within three months. Empirical antimicrobials must target Staphylococcus aureus . Diagnostic biopsy is recommended where blood cultures are non-diagnostic. Abstract: Background: Bacterial native vertebral osteomyelitis (NVO) can present diagnostic and therapeutic challenges leading to high levels of morbidity and mortality. To inform strategies aimed at improving outcomes in these patients, data are needed on the current aetiology, diagnostic interventions, management and risk factors for treatment failure. Methods: This was a retrospective, multicentre, observational cohort study of adult patients with bacterial NVO across the UK between 1st January 2015 and 31st December 2016. Infectious Disease Society of America (IDSA) guideline standards were selected and used to audit practice relating to the management of these patients. Results: A total of 286 patients were included from 40 hospitals. An organism was identified in 61% of cases by blood culture or biopsy. Of these, 51% were due to Staphylococcus aureus and 12% were due to Gram-negative bacteria. When performed, biopsy obtained a microbiological diagnosis in 50% of cases. Nearly 10% of patients required admission to an Intensive Care Unit, 20% were re-admitted to hospital, 56% experienced complications and 6% died within 90 days. Higher Charlson comorbidity index (CCI) was significantly associated with treatment failure at one month ( p = 0.004). Conclusions: This study identified opportunities to improve UK practice in the investigation and management of bacterial NVO. The range of organisms isolated supports the use of diagnostic biopsy where blood cultures are non-diagnostic, to guide antimicrobial therapy and strive to avoid treatment failure or complications. This study shows a clear need for antibiotic guidelines to reflect the current aetiology of NVO and authors support the creation of a formal registry.